Bacillus sp. is one bacterial genus causing spoilage of fishery products. The aim of the research was to find out the characteristics of Bacillus sp. from small crab (Portunus pelagicus) fresh and canned products in Company X. Five of 20 stocks or isolate fresh swimming crab and 12 stocks of bacteria cans swimming crab products namely HRN 3, NTG 3, CAD, Claw Meat 2 and Lump 1 were identified as Bacillus. Their optimal growth were at 37 C, PH 7 and salinity 3%. One starin namely Lump i can surviv - Dwi Indah Widya Yanti; Faiza A Dali (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Bacillus sp. is one bacterial genus causing spoilage of fishery products. The aim of the research was to find out the characteristics of Bacillus sp. from small crab (Portunus pelagicus) fresh and canned products in Company X. Five of 20 stocks or isolate fresh swimming crab and 12 stocks of bacteria cans swimming crab products namely HRN 3, NTG 3, CAD, Claw Meat 2 and Lump 1 were identified as Bacillus. Their optimal growth were at 37 C, PH 7 and salinity 3%. One starin namely Lump i can survive on two hours of heatig at 100 C.keywords: Bacillus sp. flat sour, swimming crab